2022
DOI: 10.3390/ijerph192013549
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Problematic Mobile Phone Use and Depressiveness and Daytime Sleepiness, as Well as Perceived Social Support in Adolescents

Abstract: (1) The aim of this study was to estimate the scale of mobile phone addiction among young adults as well as to establish whether the low level of perceived social support is related to problematic smartphone use, and whether an addictive pattern of mobile phone use is related to the prevalence of depressiveness and excessive daytime sleepiness. (2) The study was carried out using the diagnostic poll method via the questionnaire technique. Both the author’s own questionnaire and the following standardized resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“… 45 Previous findings suggest that adolescents with lower perceived social support have problematic smartphone use behaviors and significantly higher severity of depressive symptoms and daytime sleepiness. 47 The findings may support the hypothesis that problematic smartphone use might mediate the association between social support and daytime sleepiness. Therefore, the roles of loneliness and problematic smartphone use in the relationship between social support and daytime sleepiness should be explored more broadly and thoroughly.…”
Section: Introductionsupporting
confidence: 54%
“… 45 Previous findings suggest that adolescents with lower perceived social support have problematic smartphone use behaviors and significantly higher severity of depressive symptoms and daytime sleepiness. 47 The findings may support the hypothesis that problematic smartphone use might mediate the association between social support and daytime sleepiness. Therefore, the roles of loneliness and problematic smartphone use in the relationship between social support and daytime sleepiness should be explored more broadly and thoroughly.…”
Section: Introductionsupporting
confidence: 54%
“…The study of 567 Polish students showed that students in the MPD category had lower social support levels compared to non-MPD students, and that low social support levels were also positively associated with isolation and social fear among students, which led to more frequent use of mobile phones. 41 A study of 1149 Turkey college students found that those who used their phones problematic had fewer support resources from family, teachers and friends than those who used their phones normally. 72 Furthermore, a meta-analysis in China found that the negative correlation between MPD and social support in the eastern region (r = −0.152) with the best economic development level is lower than that in the central region (r = −0.216), but because of the lack of studies on the relationship between MPD and social support in the western region with the lowest level of economic development, few studies were included in the meta-analysis, so the relationship between the two is not significant.…”
Section: Discussionmentioning
confidence: 99%
“… 84 Additionally, previous studies have found that the cause of MPD in individuals is not entirely due to the lack of realistic social support resources, but also may be due to the failure to make good use of existing social support. 41 Therefore, in addition to providing adequate social support to adolescents, we should also pay attention to their emotional social support and support utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual health is influenced by many factors such as sexual behavior, attitudes, societal factors, mental, emotional and physical state [20]. Among respondents who are addicted to social media or Internet, a higher prevalence of depressive symptoms was revealed [21]. The literature review conducted by Holland et al shows increased body dissatisfaction and increased prevalence of eating disorders correlated with time spent online.…”
Section: Discussionmentioning
confidence: 99%